HUBUNGAN ETOS KERJA DENGAN KINERJA GURU DI SMK NEGERI 1 LUBUK SIKAPING - Irda Husni (Jurnal Bahana Manajemen Pendidikan, 2014)
The goal of this research are to see information about Determine theRelationship Work Ethic with The Performance of Teachers. The population is 80 employee and the sample is 66 people that taken by simple random sampling research. The instrument of this research is question with Likert scale models that had tested for validity and reliability. Data analyzed using mean score and performance level. The result of this research there isa significant relationship between work ethic with the performanceof teachers  in SMK Negeri 1 Lubuk Sikaping. Key word : Work Ethic and Teacher Performance